K: AIRLINES (1312) THE TOBACCO INSTITUTE PUBLIC AFFAIRS DIVISION PROPOSED BUDGET AND OPERATINGPLAN 1989 (890000). (Tufts Archival Research Center, 2007)
Report on the airline industry and smoking restrictions outlining background, objectives, strategies and goals, and resources. Emphasizes that the smoking ban on two hour flights will most likely be renewed and expanded to all flights unless there is action taken on behalf of the industry. Discusses research projects to demonstrate the superior ventilation systems is a more viable option than a total cigarette ban. Includes other strategies including targeting legislators and mobilizing support from sympathetic groups. Adds tentative budget for activity.